Upaya Peningkatan Profesionalitas Guru Informal Melalui Peer Observation and Evaluation - Novitasari, Rahma Kurnia; Putri, Amanda Destyana (Paedagogie, 2024)
This research aims to improve the professionalism of informal teachers in Yogyakarta through the application of the Peer Observation and Evaluation method. The research method used was Classroom Action Research (PTK) involving ten private teachers as research subjects. A qualitative approach was used to collect and analyze data in an effort to understand the impact of applying this method on improving teacher professionalism. This research was carried out in two cycles, starting from planning, implementation, observation, and reflection. Each cycle involves concrete steps in implementing the peer Observation and Evaluation method. Data was collected through observation, interviews and documentation, then analyzed using qualitative analysis. The research results show that the application of Peer Observation and Evaluation can significantly increase the professionalism of informal teachers in Yogyakarta. It was found that through the process of peer observation and evaluation, teachers can obtain constructive feedback to improve the quality of their teaching and professional abilities. Apart from that, collaboration between teachers also increases, creating a mutually supportive learning environment. This research provides an important contribution in the context of informal teacher professional development. The practical implication of this research is the importance of introducing and applying the Peer observation and evaluation method in the context of informal education as a means of improving the quality of teaching and teacher professionalism.